Layered TiO2 nanosheet‐supported NiCo2O4 nanoparticles as bifunctional electrocatalyst for overall water splitting - Raji, Vadakkekara; Rajith, Illathvalappil; Sreekumar, Kurungot (ChemElectroChem, 2018)
Exploring the generation of efficient and long‐lasting bifunctional electrocatalysts obtained from low‐cost transition metal oxides is crucial to the optimal production of hydrogen and oxygen by electrocatalytic water splitting. This study aims to demonstrate the applicability of layered TiO2 nanosheets as support for designing electrocatalysts. We have demonstrated the performance by decorating the TiO2 support with NiCo2O4 nanoparticles (NiCo2O4/TiO2) as catalysts for electrocatalytic overall water splitting. Moreover, the corrosion effect of usually used carbon‐based supporting materials can decrease the working efficiency and, thus, the overall performance of the catalysts. In this aspect, TiO2 can be a better alternative to carbon‐based systems. Layered TiO2 was synthesized at room temperature, and a simple heat treatment protocol was employed for the large‐scale synthesis of NiCo2O4/TiO2. TiO2 facilitated the formation of smaller NiCo2O4 nanoparticles, also improving the dispersion. This bifunctional electrocatalyst exhibits high OER and HER performance with a low overpotential of 309 mV and 185 mV respectively, at a current density of 10 mA cm−2. TiO2 supported catalyst also exhibits other advantages like remarkable durability in the alkaline medium along with high turnover frequency (TOF) values. This inexpensive catalyst can deliver a current density of 10 mA cm−2 at only 1.64 V with a steady performance for more than 12 h for overall water splitting. Thus, this homemade system provides a proficient and low‐cost alternative to the more expensive systems such as RuO2, IrO2 or Pt for the electrochemical water splitting applications.